EARLY-ONSET FAHR SYNDROME: A RARE PRESENTATION WITH PRIMARY HYPOPARATHYROIDISM AND EPILEPTIC SEIZURES (The Research of Medical Science Review, 2025)
Fahr syndrome is a rare neurodegenerative disorder characterized by abnormal calcium deposition in the basal ganglia and other parts of the brain, clinically manifesting with neurological and neuropsychiatric symptoms. The disease most commonly affects the middle-aged population, with the paediatric population being rarely affected. Here, we report a rare case of Fahr syndrome in a 7-year-old female with concurrent meningoencephalitis. She is a known case of congenital heart disease, who presented with a history of fever, cough, shortness of breath, and tonic-clonic seizures. On investigation, her magnetic resonance imaging (MRI) with contrast revealed bilateral calcifications in cerebral hemispheres involving the basal ganglia and subcortical white matter of frontoparietal lobes, while laboratory investigations showed hypocalcemia, hypothyroidism, and hypoparathyroidism. CT scan, at the moment, is the most reliable imaging modality to establish the diagnosis of Fahr’s syndrome. Currently, there is no definitive treatment for the disease and the management is primarily symptomatic.